The Mediating Effect of Cultural Adaptation on Product Authenticity, Price Fairness and Consumer Perceived Value - Teguh Wahyudi; Eric Harianto (University of Merdeka Malang, 2026)
PT x. is a pioneering Indonesian halal company that markets a range of halal food products in Japan. However, the company still faces challenges in maintaining product authenticity and ensuring price fairness that aligns with Japanese consumer preferences, which affects consumers' perceived value. According to the company’s data, the number of Japanese consumers who purchased Sariraya products in the past month was 4,079, averaging about 4,000 per month, indicating strong market potential but still requiring optimization of perceived value. This study aims to analyze the influence of product authenticity and price fairness on perceived value, with cultural adaptation mediating and moderating this relationship. The research uses a quantitative approach with purposive sampling, involving 278 respondents who are Indonesian diaspora consumers living in Japan and have purchased Sariraya products. The results show that product authenticity positively influences perceived value and cultural adaptation. Price fairness also positively impacts perceived value and cultural adaptation. Additionally, cultural adaptation significantly affects perceived value and strengthens the relationship between product authenticity and price fairness in shaping it. The implications of this study emphasize the importance of cultural adaptation strategies, product authenticity, and price fairness for Indonesian halal companies to enhance consumers' perceived value in the Japanese market.